AN OVERVIEW OF COLLABORATIVE LEADERSHIP: A PRELIMINARY STUDY IN THE MANUFACTURING INDUSTRY - Ramadhan, Reza Dwi; Izzati, Umi Anugerah (LPPM Universitas Bina Bangsa, 2025)
The manufacturing industry faces increasing operational complexity due to digital transformation and heightened demands for innovation and coordination. Recent studies indicate that collaborative leadership offers a viable alternative to traditional hierarchical leadership by emphasizing shared responsibility and collective decision-making (Wu et al., 2021). This preliminary study aims to examine the concept and relevance of collaborative leadership in the manufacturing industry through a qualitative review of recent literature published between 2020 and 2025. Using a thematic literature review approach, this study identifies key leadership mechanisms and organizational outcomes associated with collaborative leadership practices. The findings suggest that collaborative leadership is associated with improved team performance, innovation capability, organizational agility, and supply chain collaboration within manufacturing contexts (Shan et al., 2023). However, its effectiveness is contingent upon organizational culture, leadership readiness, and role clarity. This study provides foundational insights and highlights directions for future empirical research in manufacturing organizations.